Karakter Morfo-agronomi Tanaman Cabai Merah (Capsicum annum L.) Fase Awal Vegetatif pada Kondisi Stres Jenuh Air - Erna Siaga; Mei Meihana; Santa Maria Lumbantoruan; Jun-Ichi Sakagami; Benyamin Lakitan (Jurnal Ilmu Pertanian Indonesia, 2024)
Vegetable cultivation in tropical riparian wetland is currently suboptimal due to unpredictability of water dynamics. Chili pepper is a fruity vegetable that is often cultivated in tropical riparian wetland but is often constrained by conditions of excessive water saturation, such as shallow water tables, waterlogging and submergence in the transition period (dry to rainy season). The aim of this research was to study the morpho-agronomy of varieties of chili peppers under waterlogging stress during the early vegetative stage. A Plot Design was used in this experiment. The main plot consisted of (1) control (field capacity, regularly watering) and (2) waterlogging (simulated by adding water to the growing substrate until a thin layer of water was visible above the substrate surface during four days, followed by a seven-day recovery time during seven days). The subplot consisted of three chili pepper varieties, namely Laris, Romario, and Takanotsume (Japanese variety). Results of this study revealed that waterlogging stress significantly affected root length, number of leaves, total leaf area, chlorophyll content (SPAD), root fresh weight, shoot fresh weight, root dry weight, and shoot dry weight after stress and after recovery time. Meanwhile, chili pepper varieties were only significantly affected the total leaf area and chlorophyll content (SPAD). The total dry weight of Romario and Takanotsume before stress, after stress and after recovery did not significantly increase under waterlogging stress, whereas the total dry weight of Laris was precisely increased, indicating that vegetative growth is continuing. The Laris was categorized as one of chili pepper varieties that had medium tolerance to waterlogging stress at the early vegetative stage. Keywords: Capsicum annum L., soil plant analyses development, total dry weight, waterlogging